2017
DOI: 10.1116/1.4996434
|View full text |Cite
|
Sign up to set email alerts
|

Silver-, calcium-, and copper molybdate compounds: Preparation, antibacterial activity, and mechanisms

Abstract: Developing novel compounds with antimicrobial properties can be an effective approach to decreasing the number of healthcare-associated infections, particularly in the context of medical devices and touch surfaces. A variety of molybdate powders (AgMoO, CaMoO, CuMoO and CuMoO) were synthesized and characterized, and Escherichia coli was used as a model gram-negative bacterium to demonstrate their antimicrobial properties. Optical density measurements, bacterial colony growth, and stained gel images for protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Evidence has shown that silver molybdate and copper molybdate can enhance the abilities of antimicrobial agents in killing other Gram-negative bacteria such as E. coli . The metal ions can disrupt the cell membranes while the molybdenum oxide or molybdate oxyanion modulates the local pH to inhibit further growth 30 . It is still unclear why Typhimurium MDR strains upregulate molybdate transport genes when treated with antibiotics, but this result strengthens the argument that molybdate has a major effect on the survival of Gram-negative bacteria, especially when antimicrobial agents are present.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that silver molybdate and copper molybdate can enhance the abilities of antimicrobial agents in killing other Gram-negative bacteria such as E. coli . The metal ions can disrupt the cell membranes while the molybdenum oxide or molybdate oxyanion modulates the local pH to inhibit further growth 30 . It is still unclear why Typhimurium MDR strains upregulate molybdate transport genes when treated with antibiotics, but this result strengthens the argument that molybdate has a major effect on the survival of Gram-negative bacteria, especially when antimicrobial agents are present.…”
Section: Resultsmentioning
confidence: 99%
“…Metals have been also used for their antiseptic, wound healing and subsequently analgesic properties. The antiseptic and wound healing properties of copper were known since the time of Hippocrates; he used copper to disinfect ulcers from varicose veins and treated painful wounds and skin problems with copper and honey [4,8,[54][55][56][57]. Slaves rarely experienced rheumatic or arthritic problems and contaminated wounds because they were chained with copper strips in their wrists and ankles that protected them from such diseases [4,8,20,[54][55][56][57].…”
Section: Metalsmentioning
confidence: 99%
“…The presence of phytochemicals in the plants have tendency to reduce the heavy metals from their higher oxidation state to zero oxidation state. For the production of nanoparticles, the electron rich phytochemicals in plants acts as the building block for conversion of metallic precursor, there by replacing the toxic reducing agents [26,27] to design engineered nanomaterials in medicine, energy, electronics, etc., the green eco-friendly technique is used. The mechanism between the nanoparticles and the microorganism takes place by the electrostatic interaction of positively charged nanoparticles with that of the negatively charged microorganisms.…”
Section: Antimicrobial Activity Of Green Synthesized Copper Molybdatementioning
confidence: 99%